EVALUASI KINERJA KARYAWAN PANEN PADA PRODUKSI KELAPA SAWIT DI PT. TELEN BUKIT PERMATA ESTATE - Nanli Artin; Roby; Daryono (Politeknik Pertanian Negeri Samarinda, 2020)
This research is motivated by the importance of evaluating harvest employees in oil palm production, both in the industrial and organizational fields. This study analyzes the performance of harvest employees at PT. Telen Bukit Permata Estate, particularly in the palm oil harvesting sector. Therefore, a company must be able to manage its human resources properly in order to increase productivity in the company. This study aims to identify the characteristics of harvest employees and to evaluate the performance of harvest employees on oil palm production, based on gender, age, education and length of work. This research was conducted at PT. Telen Bukit Permata Estate in Kaubun District, East Kutai Regency. This research is focused on harvest employees who are at PT. Telen Bukit Permata Estate. This research was conducted with a descriptive method. The results of the observations made were that the average score of the questionnaire was 75.77%. Where based on the weighting scale it is included in the tofu / frequent category.